The Importance of Predicting Factors in the Surgical Outcome of Peripheral Nerve Sheath Tumors - Vetrano, Ignazio G.; Lucarella, Francesca; Dalolio, Martina; Di Cristofori, Andrea; Nataloni, Ilaria F.; Tiberio, Francesca; Gaini, Sergio M.; Grimoldi, Nadia (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2014)
Objective Peripheral nerve sheath tumors (PNSTs) are tumors arising from the neural sheath cells. Surgery plays a central role in the management of this disease, with the purpose of obtaining radical tumor's resection and at the same time providing the best outcome. We retrospectively analyzed 53 PNSTs in 42 patients in an attempt to identify some factors that may improve surgical outcome.Material and Methods Clinical, histologic, and imaging data of 42 patients with PNSTs treated at our Institute between 2001 and 2012 were collected and analyzed. We evaluated the outcome 1 month and 6 month after surgery using three clinical parameters (pain, motor deficits, and sensory deficits) in relation to different histotypes, the presence of neurofibromatosis type 1, tumor location, and duration of symptoms before treatment.Results The best functional results were observed in patients having neurofibromas; the worst outcomes were observed in patients with malignant PNSTs. The other factors were not associated with outcome.Conclusion The timing of surgery is the most important predictive factor of surgical outcome, being the only factor that allows to improve the outcome. With the current study, we want to stress the importance of treating PNSTs as soon as possible to provide the best outcome possible.
Keywords: neurofibroma; neurofibromatosis; peripheral nerve sheath tumors; schwannoma; PNST